Knowledge of Fourth Year MBBS Students about Protocols for Injections - Humayun Mirza; Ayesha Sohail; Muhammad Bin Amir; Seema Daud (Pakistan Journal of Medical Research)
Background: Injection safety is crucial for preventing infection transmission and ensuring patient safety. Adequate knowledge and adherence to protocols are vital for future healthcare professionals. Assessing medical students' knowledge can help identify educational gaps.